2023
DOI: 10.1155/2023/2721202
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxocariasis and Its Associated Risk Factors among Adult Population in Kavar District, Fars Province, South of Iran: A Cross-Sectional Community-Based Seroepidemiological Survey

Abstract: Toxocariasis as a common neglected disease is the culprit of infecting all age groups. The current cross-sectional study was designed to assess the seroprevalence of toxocariasis and risk factors associated with seropositivity of Toxocara infection among the general population of adults in the Kavar district, south of Iran. A total of 1060 participants with an age range of 35 to 70 years from the Kavar region entered the study. Manual ELISA was utilized to detect anti-Toxocara-specific antibodies in their seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
3
2
Order By: Relevance
“…In our study, we found that the rate of IgG antibodies against Toxocara in general population of Abadan and Khorramshahr cities was 12.7%. This was higher than the findings reported by recent studies in Fars (5.8%) [ 24 ], Khorasan (8%) [ 30 ], and Tehran (11.7%) [ 31 ], although our estimates were lower than the seroprevalence identified in Mazandaran (23.5%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…In our study, we found that the rate of IgG antibodies against Toxocara in general population of Abadan and Khorramshahr cities was 12.7%. This was higher than the findings reported by recent studies in Fars (5.8%) [ 24 ], Khorasan (8%) [ 30 ], and Tehran (11.7%) [ 31 ], although our estimates were lower than the seroprevalence identified in Mazandaran (23.5%) [ 32 ].…”
Section: Discussioncontrasting
confidence: 89%
“…In our study, we found that the rate of IgG antibodies against Toxocara in general population of Abadan and Khorramshahr cities was 12.7%. This was higher than the findings reported by recent studies in Fars (5.8%) [24], Khorasan (8%) [30], and Tehran (11.7%) [31], although our estimates were lower than the seroprevalence identified in Mazandaran (23.5%) [32]. Similar results were found by studies from other parts of the world: Estonia (12.0%), China (12.25%), Turkey (12.95%), Poland (13.0%), Greece (16%), and Austria (16.8%) [33][34][35][36][37][38].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…stercoralis and other helminthic parasites, cross-reaction with toxocariasis and hydatidosis sera samples was observed. Previous studies conducted in Iran have indicated a significant seroprevalence of hydatidosis and toxocariasis [ 41 , 42 ]. If we do not consider the possibility of simultaneous infection in these subjects, the cause of cross-reactivity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In neonates, congenital transmission of T. canis had also been reported previously (Ikotun et al, 2020). In different countries, the prevalence of toxocariasis in human population fluctuates between 2% and 90%, especially among tropical and developing countries (Gyang et al, 2015; Pezeshkian et al, 2023). Its seropositivity is influenced by geographical, environmental, socio‐economic and cultural factors, including age, poverty, occupation, inherited and owned cats and dogs (Aghamolaie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%